2022
DOI: 10.1093/ofid/ofac337
|View full text |Cite
|
Sign up to set email alerts
|

Notifiable Infectious Diseases Among Organ Transplant Recipients: A Data-Linked Cohort Study, 2000–2015

Abstract: Background Infections, including common communicable infections such as influenza, frequently cause disease after organ transplantation, although the quantitative extent of infection and disease remains uncertain. Methods A cohort study was conducted to define the burden of notifiable infectious diseases among all solid organ recipients transplanted in New South Wales, Australia, 2000–2015. Data linkage was used to connect tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…These findings are comparable with previous data. 11,14 The influenza-associated hospitalization rate was 38% in our study, similar to the rate in a recent cohort study from Australia 11 but lower than previously reported in a multicenter study 12 in which…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These findings are comparable with previous data. 11,14 The influenza-associated hospitalization rate was 38% in our study, similar to the rate in a recent cohort study from Australia 11 but lower than previously reported in a multicenter study 12 in which…”
Section: Discussionsupporting
confidence: 89%
“…The influenza incidence rate was highest in lung transplant recipients (40.51 per 1000 PY) and lowest in liver transplant recipients (8.47 per 1000 PY). These findings are comparable with previous data . The influenza-associated hospitalization rate was 38% in our study, similar to the rate in a recent cohort study from Australia but lower than previously reported in a multicenter study in which two-thirds of SOT recipients were admitted to the hospital.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations